Dopamine Modulates Homeostatic Excitatory Synaptic Plasticity of Immature Dentate Granule Cells in Entorhino-Hippocampal Slice Cultures - Strehl, Andreas; Galanis, Christos; Radic, Tijana; Schwarzacher, Stephan Wolfgang; Deller, Thomas; Vlachos, Andreas (Frontiers in Molecular Neuroscience, 2018)
Homeostatic plasticity mechanisms maintain neurons in a stable state. To what extent these mechanisms are relevant during the structural and functional maturation of neural tissue is poorly understood. To reveal developmental changes of a major homeostatic plasticity mechanism, i.e., homeostatic excitatory synaptic plasticity, we analyzed 1-week- and 4-week-old entorhino-hippocampal slice cultures and investigated the ability of immature and mature dentate granule cells to express this form of plasticity. Our experiments demonstrate that immature granule cells are capable of adjusting their excitatory synaptic strength in a compensatory manner at early postnatal stages, i.e., in 1-week-old preparations, as is the case for mature granule cells. This ability of immature dentate granule cells is absent in 4-week-old slice cultures. Further investigations into the signaling pathways reveal an important role of dopamine, which prevents homeostatic synaptic up-scaling of immature granule cells in young cultures, whereas it does not affect immature and mature granule cells in 4-week-old preparations. Together, these results disclose the ability of immature granule cells to express homeostatic synaptic plasticity during early postnatal development. They hint toward a novel role of dopaminergic signaling, which may gate activity-dependent changes of newly born neurons by blocking homeostasis.